Determination of Internalization of Moral Work Culture in Constructing the Integrity of East Java Social Service Apparatus - Sri Kamariyah; Nur Rusydina bt Khadzali; Aris Sunarya; Nihayatus Sholichah; Widyawati Widyawati (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This research aims to analyze the determination of the internalization of BerAKHLAK work culture in constructing apparatus integrity within the Social Services Department of East Java Province. In the context of modern bureaucratic transformation, Civil Servants (ASN) are required to have a strong work culture foundation as a moral compass to avoid practices that deviate from professional ethics. The Social Services Department possesses unique characteristics as it interacts directly with vulnerable social groups, necessitating personnel with unwavering integrity and moral immunity against the temptation of abusive authority. Utilizing a qualitative descriptive approach with a case study design, this research dissects the phenomenon of value internalization holistically through in-depth interviews, observation, and documentation. The results indicate that the internalization process of BerAKHLAK (Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative) is carried out through a social construction dialectic encompassing stages of externalization, objectification, and internalization. Phenomenological findings suggest a paradigm shift from formalistic integrity toward substantive integrity, where values ​​such as Accountability and Loyalty are no longer viewed merely as regulatory burdens but as manifestations of moral responsibility rooted in individual conscience. The habituation process through routine actions, such as consistently precise data verification, has created an "ethical sedimentation" that transforms honest behavior into an instinctive or automatic self-governing action. Furthermore, the Harmonious and Collaborative dimensions have successfully established peer-supervision mechanisms and a collective social identity that strengthens the organization's moral fortress through collective social shame against deviations. The integration of Competent and Adaptive values ​​also proves to be a primary determinant in mitigating ethical risks, where technical professionalism encourages personnel to remain transparent despite complex field pressures. Overall, the internalization of BerAKHLAK work culture has successfully reconstructed the integrity of the East Java Social Services apparatus into a stable social reality, which not only transforms work methods but also builds public trust through quality and equitable service.